1997
DOI: 10.1097/00004032-199704000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Radon Measurements in the Gran Sasso Underground Laboratory

Abstract: Systematic radon monitoring in the Gran Sasso Underground Laboratory was performed in order to determine the background radon contribution to the sophisticated experimental apparatus and to check health physics standards for the personnel. As expected, the radon concentrations were found to depend strongly on the ventilation in the three experimental halls. Considerable reductions in the radon concentrations were obtained in 1993, when fresh air was drawn into the laboratory through a pipe and exhaust air was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…An average value of 28 Bq/m 3 (0.77 pCi/l) was obtained [6]. As a reference, this can be compared with the maximum acceptable 45 Bq/m 3 in US households, or with the lowest values achieved in the Gran Sasso underground laboratory, 20-50 Bq/m 3 [7]. Similar results have been obtained in April 1999.…”
Section: Airborne Radonsupporting
confidence: 59%
See 1 more Smart Citation
“…An average value of 28 Bq/m 3 (0.77 pCi/l) was obtained [6]. As a reference, this can be compared with the maximum acceptable 45 Bq/m 3 in US households, or with the lowest values achieved in the Gran Sasso underground laboratory, 20-50 Bq/m 3 [7]. Similar results have been obtained in April 1999.…”
Section: Airborne Radonsupporting
confidence: 59%
“…The radon concentration in the atmosphere of the capsule was measured during three weeks in January 1998 using a RAD7 NITON radonmeter (a self-contained continuousmonitoring solid state alpha detector [5] [7]. Similar results have been obtained in April 1999.…”
Section: Airborne Radonmentioning
confidence: 94%
“…However, most significantly, the low level of 238 U contributes to a low ambient background from airborne 222 Rn of only 2.4 Bq m −3 [10]. This is significantly lower than the lowest radon activity values measured in the Gran Sasso laboratory of (20 -50) Bq m −3 [11].…”
Section: Boulby Underground Laboratorymentioning
confidence: 71%
“…More detailed studies on the radon concentration in Callio Lab are also needed since the reported radon level (50-300 Bq/m3) [22] is at least 10-15 times higher than that in LNGS [26]. It is known as well that the radon-level in a lab generally varies quite a lot.…”
Section: Radon Effectmentioning
confidence: 99%